Rope climbing robot - Thanachelvan, Rajan (2010)
This project is all about developing a rope climbing robot which prioritizes in only one task of manipulating its position on a rope. The robot is assigned to perform climbing motions on a vertical rope in a limited amount of time. The objective here is to produce an efficient, low powered and cost effective self climbing robot that is able to reach the top of the rope in the least amount of time. All the power sources are on-board and the robot will be totally mobile (no cords or wires attached from circuits other then on board). The climber robot can be attached with external circuits to serve various tasks such as by fixing a small video camera to offer "visual access" in places where access by human presence is difficult and dangerous.